2007
DOI: 10.1007/s12013-007-0039-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of Advanced Glycation End Products in Hypertension and Atherosclerosis: Therapeutic Implications

Abstract: The vascular diseases, hypertension and atherosclerosis, affect millions of individuals worldwide, and account for a large number of deaths globally. A better understanding of the mechanism of these conditions will lead to more specific and effective therapies. Hypertension and atherosclerosis are both characterized by insulin resistance, and we suggest that this plays a major role in their etiology. The cause of insulin resistance is not known, but may be a result of a combination of genetic and lifestyle fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
8

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 190 publications
(262 reference statements)
1
57
0
8
Order By: Relevance
“…It is closely associated with atherosclerosis and vascular function, and in the brain results in hypoperfusion and ischemic conditions of the nucleus basalis of Meynert. The use of targeted molecular mechanisms and dietary methods and therapies is grounded in reducing free radicals and associated oxidative stress-related damage initiating hypertension [Vasdev et al 2007]. …”
Section: Modulation Of Cholesterol and Vascular-related Risk Factorsmentioning
confidence: 99%
“…It is closely associated with atherosclerosis and vascular function, and in the brain results in hypoperfusion and ischemic conditions of the nucleus basalis of Meynert. The use of targeted molecular mechanisms and dietary methods and therapies is grounded in reducing free radicals and associated oxidative stress-related damage initiating hypertension [Vasdev et al 2007]. …”
Section: Modulation Of Cholesterol and Vascular-related Risk Factorsmentioning
confidence: 99%
“…Indeed, AGE form crosslinks with low-density lipoprotein (LDL), which become more atherogenic and less susceptible to absorption and subsequent clearance. In addition, LDL modified by AGEs is more easily captured by receptors located on macrophages, generating foam cells (cells with fat droplets and cholesterol) (Hartog et al, 2007;Vasdev et al, 2007) (Figure 7). It has also been suggested that AGEs are involved in neurodegenerative diseases, such as Alzheimer and Parkinson (Grillo & Colombato, 2008;Sato et al, 2006b), arthritis (Vytásek et al, 2010), loss of bone mass (Ding et al, 2006) and promotion of changes in the function and/or structure of DNA and RNA molecules .…”
Section: Biological Activity Of the Maillard Reaction Products (Mrps)mentioning
confidence: 99%
“…The high nutrient density (HND) diet emphasizes micronutrients (phytochemicals and antioxidants) from greens, fruits, nuts/seeds and beans/legumes, the latter containing high amounts of viscous fiber and resistant starches. The HND diet incorporates features of other dietary interventions, but is designed to create advantages from multiple mechanisms, including the effect that high micronutrient food has in reducing cravings and overeating, and on lowering oxidative stress [8] and deposition of advanced glycation end products [9,10].…”
Section: Introductionmentioning
confidence: 99%